Penatalaksanaan Tuberkulosis Paru Putus Obat Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Sukaraja - Chyntia Saputri; Sahab Sibuea; Rasmi Zakiah Oktarlina (Medula, 2020)
A holistic and comprehensive family medicine approach in detecting internal-external factors, prioritizing family-approached and patient centers is hoped to be able to improve the quality of life of patients. In this case, diagnosis and management were carried out with the concept of family medicine. Primary data were obtained through history taking, physical examination and home visits. Secondary data comes from patient medical records. The case of the patient, Mrs. 26 years old, had drug withdrawal TB (ICD X A15.0). The complaint was felt to have reappeared since three months ago, but the patient still had functional degree 2 in carrying out daily activities. Patients have internal risk factors, namely the patient's lack of knowledge of the disease, inappropriate lifestyle, curative treatment behavior and lack of medication adherence. External factors possessed by the patient are a family with low income (ICD10 – Z59.6), poor lighting, poor ventilation in the house, a densely populated home environment, inadequate cleanliness of the home environment and contact with patients with prolonged coughs. Handling and treatment efforts in a holistic and comprehensive manner using a family medicine approach in the form of education on causes, transmission, treatment and prevention of disease.